Priority Determination of Marketing Mix at Nadhira Napoleon Gift Shops in Pekanbaru Using the Analytic Network Process Method - Putri, Hilma Anisa; Restuhadi, Fajar; Dewi, Novia (Jurnal AGRISEP, 2023)
Nadhira Napoleon is one of the shops that houses the largest and most comprehensive chain of souvenir shops in Pekanbaru City. In carrying out its business certainly can not be separated from a good marketing strategy. One of the marketing strategies that is often carried out by a company is the 7P marketing mix. This study aims to determine marketing mix priorities at Nadhira Napoleon's Souvenir Shop. Data analysis is carried out by means of weighting from experts, distributors and consumers using the ANP (Analytic Network Process) method. The results of the data analysis show that the Place mix is ​​the first priority carried out by the Nadhira Napoleon Gift Shop with a weight of 0.227 with a percentage of 22.72%. Followed by the place marketing mix which occupies the first position, namely out lite Location with a weight of 0.085 with a percentage of 17. Furthermore, the alternative that is the first priority of the marketing mix is ​​to expand market share with a weight of 0.247 and a percentage of 49.4. Gift shop Nadhira Napoleon set up a gift shop which is strategically located, with easy access for consumers. Starting from the layout, shop settings, traffic flow conditions such as congestion, and parking lots for easy access in and out of vehicles and the level of security is very trustworthy, so that the Nadhira Napoleon Gift Shop can dominate the market share for souvenir products.